Adopting Co-operate Social Responsibility Initiatives for Sustainability (International Journal of Food and Nutritional Sciences, 2022)
While I have always been interested in business and entrepreneurship and researchon them, this period has solidified my decision. I had been looking foropportunities to research more as research scholar at companies during mydoctorate but due to the pandemic, these opportunities were very limited.However, what impressed me most was how the Indian corporate sector, includingIndian companies of all sizes and multinationalcompanies in India,hasgoneoutofitsway to help thosehave lost their jobs orareexperiencingdifficultiesin their families.I realized that CSR is animportantaspect of business, especially in India, and I wanted to explore it further.My research paper is on CSR, type, scope, top 2 Indian companies in termsof CSRspend. It also has case studies of two large Indian companies that I admire for theirdiversity,ITC and TCS, Overall, I am impressed not only by the scale and diversityof CSR activities and budgets for Indian companies, but also by how they gobeyond what is prescribed.